School of English for Applied Economics - L. K. Raitskaya (Vestnik MGIMO-Universiteta)
Department of English Language № 5 was created at the Institute of Foreign Economic Relations in 2000, and since 2011 it has been working with the students of the Department of Applied Economics and Commerce. Department of English Language № 5 prepares training materials, multimedia courses, manuals and tutorials based on the up-to-date educational technologies. A series of textbooks and teaching materials was recently published by the Department. They are widely used in teaching business communication for Economists. This series include textbook "Commercial correspondence and documentation in English" by L.K. Raitskaya and L.V. Korovin, textbook "Business English with the use of case studies (case studies)" edited by O.V. Desyatova? and textbook "Two-way translation of dialogues commercial content"by O.V. Desyatova.